1992
DOI: 10.1093/ndt/7.7.597
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein (a) in patients with proteinuria

Abstract: Lipoprotein(a) (Lp(a)) has recently been recognized to be a risk factor for coronary heart disease. Lp(a) median values in the absence of renal disease are around 10 mg/dl. Higher levels (greater than or equal to 30 mg/dl) correlate with the occurrence of coronary heart disease, particularly in the presence of elevated cholesterol. We have studied Lp(a) in 76 adults with proteinuria. Fifty had glomerular diseases and 26 non-glomerular diseases, with renal function varying from normal to advanced chronic renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 0 publications
1
26
0
1
Order By: Relevance
“…Elevations in Lp(a) serum levels have been documented in adults with proteinuria (24)(25)(26), adults with end-stage renal failure treated by hemodialysis (27), renal allograft recipients (28), and children (33) and adults (34) with diabetes mellitus. In addition, alcohol intake (35) and possibly treatment with corticosteroids (25) may have an effect on serum Lp(a) levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevations in Lp(a) serum levels have been documented in adults with proteinuria (24)(25)(26), adults with end-stage renal failure treated by hemodialysis (27), renal allograft recipients (28), and children (33) and adults (34) with diabetes mellitus. In addition, alcohol intake (35) and possibly treatment with corticosteroids (25) may have an effect on serum Lp(a) levels.…”
Section: Discussionmentioning
confidence: 99%
“…Lp(a) can be detected in umbilical cord blood and serum of newborns (20)(21)(22), and a gradual rise in serum levels has been observed between the ages of 2 and 13 y (23). Previous studies in adults reported increased Lp(a) levels in patients with proteinChronic renal disease is often accompanied by severe dyslipi- (24)(25)(26) and in patients treated with hemdialysis (27) and demia, a known risk factor for cardiovascular disease. In adults, renal transplantation (28).…”
Section: ~H~ Distribution Of Lp(a) Levels In Normal Subjects Wasmentioning
confidence: 99%
“…Significantly higher cholesterol levels are present in the more buoyant LDL fractions (fractions 12-18) of the intensively treated group. A trend can be seen toward lower cholesterol content in the intermediate-density lipoprotein (IDL) fractions (fractions [19][20][21][22][23][24][25][26][27][28][29][30] in the intensively treated group, although this did not reach statistical significance.…”
Section: Dgucmentioning
confidence: 99%
“…Lp(a) levels have been shown to be higher in familial hypercholesterolemia [13], chronic renal failure [14][15][16][17][18][19], and nephrotic syndrome [20][21][22][23][24][25], and lower levels have been reported in cirrhosis [26]. How Lp(a) levels might be affected by IDDM and its complications and whether Lp(a) contributes to CAD [27,28] in this population remain controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly it could also be thrombogenic in large vessels other than the coronary arteries, for example the renal veins. Finally it could also have a role in the progression of renal disease (17).…”
Section: Discussionmentioning
confidence: 99%